2021
DOI: 10.3390/jcm10020363
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Hemoglobin and Renal Prognosis of IgA Nephropathy

Abstract: Immunoglobin A (IgA) nephropathy causes chronic kidney disease worldwide. Therefore, identifying risk factors associated with the progression of IgA nephropathy is crucial. Anemia is a common complication of chronic kidney disease; however, few studies have investigated the effect of serum hemoglobin on the renal prognosis of IgA nephropathy. This study aimed to determine the effect of serum hemoglobin on the progression of IgA nephropathy. We retrospectively analyzed 4326 patients with biopsy-proven IgA nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
2
11
1
Order By: Relevance
“…There was also no statistically significant interaction of hemoglobin between men and women (P interaction = 0.8543). The interaction of hemoglobin between men and women was also consistent with the findings of Oh, T R et al [24]. Unlike them, our study found a statistically significant relationship between hemoglobin and CKD progression in both male and female patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was also no statistically significant interaction of hemoglobin between men and women (P interaction = 0.8543). The interaction of hemoglobin between men and women was also consistent with the findings of Oh, T R et al [24]. Unlike them, our study found a statistically significant relationship between hemoglobin and CKD progression in both male and female patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, in their further subgroup analyses, reduced serum hemoglobin was an independent risk factor for IgA nephropathy progression only in women(HR = 0.875, 95%CI: 0.768-0.998, P = 0.046), while in men, the HR and 95%CI were 0.937,0.858, 1.023, respectively. There was no statistically significant interaction of serum hemoglobin between men and women (P interaction = 0.177) [24]. In our research, having a medium sample size, the multivariable-adjusted Cox proportional hazards models showed a negative association between Hb and renal composite endpoint, consistent with those two studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another independent risk factor we identified was female sex. Oh et al found that in IgA nephropathy, female sex was strongly associated with decreased haemoglobin [ 30 ]. Poudel et al also found a high incidence of anaemia in women with CKD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%